Modified disturbance observer-based control for stable multivariate processes with multiple time delays. (December 2018) - Du, Xinghan; Jin, Qibing
Highlights: A modified multivariate DOB control strategy is proposed. The method for designing the modified inverse model is provided. The controller for disturbance rejection is designed analytically by optimizing 2 norm of output. Controller parameters are determined by considering robustness and performance. Abstract: In this study, the authors propose a modifiedd isturbanceo bserver-b ased (DOB) control strategy for input load disturbance rejection, in cases of stable multivariate processes with multiple time delays. Unlike the existingm ultivariated isturbanceo bserver-b ased (MDOB) control strategies using approximate inverse model to estimate external disturbances, the proposed MDOB control strategy instead designs a V canonical structure, which can estimate the external disturbances rapidly and exactly. Based on the V canonical structure, the controllers for disturbance rejection are designed analytically by minimizing 2-norm of the outputs caused by disturbances. The tunable parameters of the controllers are determined by considering both the control performance and robustness. Simulation studies demonstrate the effectiveness of the proposed method.